Avian toxicoses: a review - Vetere, Alessandro; Di Ianni, Francesco; Gavezzoli, Martina; Cococcetta, Ciro (Frontiers in Veterinary Science, 2025)
Bird species, both domestic and wild, are frequently exposed to a wide range of toxic compounds. Toxicosis in avian patients is often a clinical challenge. Diagnosis often relies on history and clinical signs because specific tests for most toxicants are not available in clinical practice, or they require unsustainable blood volume for small avian species. The management of toxicoses consists of patient stabilization, decreasing toxin absorption, improving its elimination, and supporting therapy. This literature review provides an outline of the most common toxicoses in birds, as well as their diagnosis and possible treatments.